The Nap family proteins, CG5017/Hanabi and Nap1, are essential for Drosophila spermiogenesis. Issue 7 (20th February 2013) - Kimura, Shuhei
Abstract : Spermiogenesis is a dynamic process leading to alterations in cell morphology. In spermiogenesis, the roles of the histone chaperones are largely unknown. Here, I report the unexpected roles of two Nap family proteins, CG5017/Hanabi and nucleosome assembly protein 1 (Nap1) in Drosophila . Hanabi is mainly localized in the cytoplasm, and the hanabi mutant shows fully scattered nuclei and abnormality of nuclear shaping in spermatid elongation. In contrast, Nap1 is localized at the apical tip of the sperm head, and the nap1 mutant exhibits disruption of the nuclear bundle in the later stage. These findings imply that Nap family proteins might individually sustain cytoskeleton‐based morphogenesis, rather than histone biogenesis. Abstract : ► Hanabi is a testis‐specific Nap family protein. ► Hanabi mutant shows scattered and abnormally shaped nuclei in spermatid. ► Nap1 mutant shows disruption of the nuclear bundle in the later stage.